Obtenção e caracterização do aço FE-0,25%c com adição de TI pelo processo de metalurgia do pó - Bezerra, Daniel Alves (Universidade Federal Rural do Semi-Árido, 2019)
The rising cost and volatility of metals has led to the development of new alloying systems for steels manufactured by powder metallurgy. An addition of microalloying elements such as titanium provides an easy way to achieve a good combination of excellent durability and strength through grain size control and precipitation hardening. This work investigated the influence of titanium on the microstructure and the mechanical behavior of microalloyed steels manufactured by powder metallurgy. Five samples were made with titanium contents ranging from 0 to 0.20%. To measure the microstructure and mechanical strength of sintered samples, optical microscopy and Vickers hardness tests were performed. The results indicate that, as additions of different titanium percentages, they optimize as properties of the material, increasing its hardness and decreasing its porosity.
Monografia
Keywords: Metalugria do pó; Sinterização; Aços Microligados; Titânio; ENGENHARIAS::ENGENHARIA MECANICA